Depressive symptoms in individuals with burns: A Brazilian study - Sandra Renata Pinatti de Moraes; Joao Fernando Marcolan (Wolters Kluwer Medknow Publications, 2021)
Objectives: The objective of the study is to analyze the presence and intensity of depression symptoms in burn survivors. Methods: This is a descriptive and quantitative study, with 36 participants with burns admitted to a referral center in Londrina/PR, between January 2016 and May 2019. Interviews were conducted at two moments after hospital discharge with the application of psychometric scales for depression (Beck, Hamilton, and Montgomery-Asberg) and a semi-structured questionnaire for information on sociodemographic data. Data analysis was performed using statistical tests. Results: Most participants presented moderate and severe depressive symptoms, which were higher in the second interview. Regardless of having a previous diagnosis, there was an increase in the intensity of depressive symptoms from the first to the second assessment due to dissatisfaction with self-image, but without a significant association with sociodemographic variables. Most participants reported not wearing clothing to cover the injury and not worrying about hiding the injury. Conclusion: The expressive majority of the participants had depressive symptoms, the majority of which were of moderate and severe intensity.